A framework for developing urban forest ecosystem services and goods indicators (2011)
The social and ecological processes impacting on urban forests have been studied at multiple temporal and spatial scales in order to help us quantify, monitor, and value the ecosystem services that benefit people. Few studies have comprehensively analyzed the full suite of ecosystem services, goods (ESG), and ecosystem disservices provided by an urban forest. Indicators, however, are one approach that could be used to better understand the structure of an urban forest, the suite of ESG provided by urban forests, and their influence on human well-being using a simple, innovative and repeatable metric. This study presents a framework for developing indicators using field data, an urban forest functional model, and the literature. Urban tree and soil indicators for groups of ecosystem functions were used to statistically analyze the effects of urban morphology and socioeconomics on urban forest ESG. Findings show that the most influential ESG indicators were tree cover, soil pH, and soil organic matter. Indicators were significantly influenced by land use and time since urbanization, while analyses of property values and household income did not yield any particularly significant results. The indicators presented in this paper present a first approach to non-monetary valuation of urban forest ESG and can be used to develop urban forest structure management goals and to monitor the effects of urban greening policies on human well-being.